Digitalisasi dan Dampaknya Bagi Perkembangan Psikologi Remaja Kristen - Ricu Sele; Wahyu Wijiati (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2024)
Technology with all its developments has become an integral part of the lives of today's teenagers. The extensive use of technology, such as smart phones, social media, gaming, and other things related to digitalization, can have a significant impact on the psychological development of teenagers. In this situation, the church, family and Christian ministry institutions have a very important role to play, which is why a correct understanding of digitalization and all the impacts it has, both positive and negative, is needed. Uncontrolled use of technology can affect the mental health of Teenagers. This influence can take the form of watching negative content, deviant behaviors of bullying or body shaming, online gambling, and other shows that can have an impact on the psychology of Christian teenagers. This impact is what the author will examine in this paper. The author uses a descriptive method where the author will use journals and literature relevant to this writing. These literature sources are used as sources of information in order to analyze and describe the research in accordance with this journal. The author hopes that this research can provide information and contributions for churches, families, and Christian institutions to approach, assist and even handle teenage youth so that digitalization can have a spiritual and positive impact on Christian youth.